Pengaruh Revolusi Amerika Terhadap Pembentukan Identitas Nasional di Amerika Serikat - Sitepu, Maria Maharani; Tariga, Gema Persada; Pratama, Dian; Natasha, Kinanti Naya; Piliang, Putri Hasanah; Rumahorbo, Ruth Debora; Raunaq, Ulya Salisa (Medan Resource Center, 2024)
The American Revolution (1775-1783) was a pivotal event in United States history that ended British colonial rule and initiated the formation of a strong national identity for the new nation. This research aims to explore how the American Revolution contributed to the formation of national identity in the United States. Through historical and contextual analysis, the study identifies key factors such as the influence of Enlightenment ideas, the role of revolutionary figures, and the development of political and cultural institutions that became the foundation of national identity. The study also examines the social and political impacts of the Declaration of Independence and the formation of the United States Constitution, which served as the legal basis and symbol of national unity. The findings show that the American Revolution not only achieved political independence but also inspired values of freedom, egalitarianism, and democracy, which are central to the national identity of the United States. This research provides insights into the historical process of national identity formation and its relevance to contemporary national dynamics.